TRANSFORMASI NILAI-NILAI PANCASILA DALAM PEMBAHARUAN HUKUM PIDANA NASIONAL - Ade Mahmud (Jurnal Hukum Mimbar Justitia, 2018)
The condition of the national criminal law as a legacy of the Dutch Colonial is deemed inconsistent with Pancasila values so that the effort to reform the criminal law (KUHP) continues to be voiced through the re-formulation of criminal law policy. The results (1) Renewal of national criminal law based on mission (a) Decolonization through "recodification" (b) Democratization of criminal law (c) Consolidation of criminal law to avoid conflict of norms (antinomy normen) (d) Adaptation and harmonization of criminal law with the development of criminal law science. (2) The transformation of idea / paradigm / value of Pancasila in the RKUHP can be pursued through a penal reform strategy that requires (a) Identification of problems in the form of old norms that are considered inconsistent with the social condition of the community. (b)Â  the basis / value that lies behind the old chapter (ide / paradigm of individualism / liberalism) and change / replace it by applying the idea / paradigm / value of Pancasila in the new draft formulation of the article. (c) Transform the values of Pancasila into the formulation of a new chapter and revoke the formula / value paradigm of value contained in the old chapter.Keywords: Transformation, Pancasila, Criminal Law Update.